2021
DOI: 10.1016/j.artd.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Does Activity Level After Primary Total Hip Arthroplasty Affect Aseptic Survival?

Abstract: Background The purpose of this study is to evaluate survivorship and outcomes of high-activity patients compared to low-activity patients after total hip arthroplasty. Methods A retrospective review identified 2002 patients (2532 hip) that underwent a primary total hip arthroplasty with vitamin E–infused highly crosslinked polyethylene liner. Patients were divided into 2 groups based on their University of California Los Angeles (UCLA) activity level: low activity (LA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Yet after adjusting the groups for age, BMI, CCI, ASA, and preoperative activity, the low-activity group still showed inferior revision-free survival compared to the moderate-as well as the high-activity group. Similar findings were reported by Crawford et al in 2021, who found that a higher activity level (defined as UCLA > 6) was a significant factor for improved implant survival after THA [18].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Yet after adjusting the groups for age, BMI, CCI, ASA, and preoperative activity, the low-activity group still showed inferior revision-free survival compared to the moderate-as well as the high-activity group. Similar findings were reported by Crawford et al in 2021, who found that a higher activity level (defined as UCLA > 6) was a significant factor for improved implant survival after THA [18].…”
Section: Discussionsupporting
confidence: 90%
“…The risk of aseptic loosening due to implant wear is frequently cited as an argument against high activity [5,6,19,37]. However, the current findings suggest that, despite the biomechanical proof of increased wear due to increased forces, actual clinical findings may not justify general advice against high physical activity [17,18]. The risk associated with being highly active in general and participating in certain desired sports specifically should be evaluated and discussed together with the patient on an individual basis rather than imposing generalized restrictions.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Fretting and the increased cyclic loading of the interfaces result in creating an environment conducive to corrosion. This finding raises a significant concern for the performance of modular implants in active patients in the long term [56][57][58][59][60][61].…”
Section: Demographics Meanmentioning
confidence: 99%